The role of customs procedures in reduction of maintenance, repair and overhaul costs in the aviation industry - Natalia Płaza; Deimantė Žilinskienė (Financial Internet Quarterly, 2022)
Scope of the article will cover analysis of special customs procedures and other facilitations that can be used in MRO business. The two research questions that are answered in the paper are: what customs procedures can be used, how they work and if those can reduce costs of MRO operations significantly. There are two research methodological approaches used in this article: qualitative and quantitative. Results show a great difference in savings between two variants, in which one would present a very basic level of special customs procedures usage and a variant in which all presented possibilities would be applied. Research results showed many possibilities for changes in the customs strategy of a company interested in evolving it and generating savings from many facilitations due to usage of special customs procedures as well as a compact explanation of how the application of a special procedures process looks. This article may be interesting for both: scientists and specialists working in the field of customs as well as for the companies working internationally with a lot of imported materials needed to perform work on an engine or aircraft.
Keywords: A12; C00; C53; 330; customs; management; aviation; savings; finance